A qualitative exploration: tenants of green office building in Kuala Lumpur / Nor Adibah Mohd Arif and Noruelin Huri - Mohd Arif, Nor Adibah; Huri, Noruelin (UiTM Press, 2023)
It has been suggested that selecting the building that is perceived by the market may not be the ultimate factor in the office location decision. The green features were previously categorized as an important consideration for office occupation decision-making. This study seeks the understanding and reason behind tenants' choice in adding up value to their business in Kuala Lumpur. Tenants' decisions are based on the post-occupancy of the tenancy in a green office building. In this paper, we identify factors' influencing tenants to occupy green office buildings using a mixed industry of in-depth interviews in Kuala Lumpur. The interview reveals the factors the tenants consider when choosing a green office building and further explores the qualitative reasons for those choices. Tenants' preferences were displayed as locational behaviour, including the building features, cost, image, and branding. This research revealed the thirteen tenants using purposive sampling and snowball sampling. The study identifies the factors that are influenced by the company's profile. This in-depth interview will provide the foundation of a future comprehensive survey of office tenants on their choices of green office buildings.